1996
DOI: 10.1021/ic950351s
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Reactivity Mode of Coordinated Oximes:  Platinum(IV)-Assisted Ring Closure by Reaction with Acetone

Abstract: The platinum(II) complexes trans-[PtCl(2)(RR'C=NOH)(2)], where R = R' = Me, RR' = (CH(2))(4) and (CH(2))(5), react with m-chloroperoxybenzoic acid in Me(2)CO to give the platinum(IV) complexes [PtCl(2)(OCMe(2)ON=CRR')(2)] in 50-60% yields. The complexes [PtCl(2)(OCMe(2)ON=CRR')(2)] were characterized by elemental analysis, EI-MS, and IR and Raman spectroscopies; X-ray structure analyses were performed for both trans-[PtCl(2)(OCMe(2)ON=CC(4)H(8))(2)] and trans-[PtCl(2)(OCMe(2)ON=CC(5)H(10))(2)]. The former comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Two possible formulations may be envisaged for this product, namely an η 2 -acetone adduct of a monohapto W−iminoacyl H or a metallacyclic structure I derived from a [3 + 2] cycloaddition of the W−C(N- i -Pr)Me fragment to a molecule of acetone. Precedent for the latter possibility can be found in previous work by Werner and co-workers. , In order to unambiguously characterize this material, X-ray studies were attempted. While crystals of 8cad suitable for this determination could not be obtained, the related complex 9cad , isolated after the analogous reaction of CpWMe(CO) 2 (CNMe) ( 9al ) in acetone, readily provided single crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Two possible formulations may be envisaged for this product, namely an η 2 -acetone adduct of a monohapto W−iminoacyl H or a metallacyclic structure I derived from a [3 + 2] cycloaddition of the W−C(N- i -Pr)Me fragment to a molecule of acetone. Precedent for the latter possibility can be found in previous work by Werner and co-workers. , In order to unambiguously characterize this material, X-ray studies were attempted. While crystals of 8cad suitable for this determination could not be obtained, the related complex 9cad , isolated after the analogous reaction of CpWMe(CO) 2 (CNMe) ( 9al ) in acetone, readily provided single crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Similar processes involving metal complexes are also known although scarce. 14,15 Metal-mediated iminoacylation of oximes is an even lesser explored area, and only one example of such a reaction has been published so far. Thus, Grigg et al 16 and concurrently Zerbib et al 17 reported one-pot multistep processes between oxovanadium(IV) aldoxime and ketoxime complexes, for example [VO{C 6 H 4 (O)CHdNOH} 2 ], under treatment with acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…As far as addition reactions of oximes are concerned, it is well-documented that oximes are ambidentate nucleophiles and their N - or O -alkylation, acylation, and arylation have been extensively studied and reviewed in organic chemistry. Similar processes involving metal complexes are also known although scarce. , Metal-mediated iminoacylation of oximes is an even lesser explored area, and only one example of such a reaction has been published so far. Thus, Grigg et al and concurrently Zerbib et al reported one-pot multistep processes between oxovanadium(IV) aldoxime and ketoxime complexes, for example [VO{C 6 H 4 (O)CHNOH} 2 ], under treatment with acetonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have observed that the same platinum(II) complexes trans- [PtCl 2 (RR‘CNOH) 2 ], where R = R‘ = Me and RR‘ = (CH 2 ) 4 and (CH 2 ) 5 , react with MCPBA in Me 2 CO to give the platinum(IV) compounds [PtCl 2 (OCMe 2 ONCRR‘) 2 ] without change in the oxidation state of the oxime N atom …”
Section: Introductionmentioning
confidence: 99%